2016
DOI: 10.1021/acs.langmuir.6b01746
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Lipidic Cubic Phase Nanoparticles with Lipid Membranes

Abstract: The interactions of liquid-crystalline monoolein (GMO) cubic phase nanoparticles with various model lipid membranes spread at the air-solution interface by the Langmuir technique were investigated. Cubosomes have attracted attention as potential biocompatible drug delivery systems, and thus understanding their mode of interaction with membranes is of special interest. Cubosomes spreading at the air-water interface as well as interactions with a monolayer of 1, 2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Namely, the incorporation was hindered in more organised layers, and enhanced in porous layers. 36 Parallel results were demonstrated for phytantriol (Phy) cubosomes on 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayers. The results showed an accumulation/exchange of materials up to 82% cubic phase material in the bilayer.…”
Section: Introductionmentioning
confidence: 79%
“…Namely, the incorporation was hindered in more organised layers, and enhanced in porous layers. 36 Parallel results were demonstrated for phytantriol (Phy) cubosomes on 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayers. The results showed an accumulation/exchange of materials up to 82% cubic phase material in the bilayer.…”
Section: Introductionmentioning
confidence: 79%
“…The interaction with the lipid film interface was enhanced at acidic pH, which causes a switch to cubosomes structures. [61][62][63][64] Based on the above, it can be concluded that the interfacial interaction between the DOX-BJO-LCNPs with the model lipid membranes appears to be stronger for the case of the cubic phase (cubosome) nanocarriers at pH 6.8. Considering the established pH sensitivity of the liquid crystalline carriers and the pH-induced structural transformations, it can be expected that the interactions of the DOX-BJO-LCNPs with the cancer cells will be more pronounced under acidic pH conditions (corresponding to the pH of simulated tumor microenvironment).…”
Section: Interaction Of Liquid Crystalline Nanoparticles With Lipid Membrane Interfacesmentioning
confidence: 85%
“…Other salts' compression isotherm plots are shown in Figure 4 [37][38][39]. The information provided by the -A isotherm, the elasticity modulus, was determined to be evaluated in more detail as follows.…”
Section: Effect Of Sub-phase On Monoolein Lipid Langmuir Monolayermentioning
confidence: 99%
“…Many researchers conduct the elasticity modulus recognition based on Eq. 1 for the selection of parameters based on the physical state of the lipid monolayer, in their extension analysis toward the Langmuir isotherm [37][38][39]. The information provided by the -A isotherm, the elasticity modulus, was determined to be evaluated in more detail as follows.…”
Section: Determination Of Elasticity Modulus and Surface Compressibilmentioning
confidence: 99%